Gas Chromatography/Mass Spectrometry characterization and antinociceptive effects of the ethanolic extract of the leaves from Clusia minor L. - Raisa Mangas; Gledys Reynaldo; Maria T. Dalla Vecchia; Kendely Aver; Leonardo G. Piovesan; Adonis Bello; Idania Rodeiro; Angela Malheiros; Marcia M. de Souza; Roberto Menéndez (GarVal Editorial Ltda., 2019)
Context: The search of new substances with analgesic properties has grown in the last years. Brazil and Cuba have a big biodiversity allowing the study of several plants with potential pharmacological activities. Aims: To evaluate the chemical composition and potential antinociceptive effect of the ethanolic extract from Clusia minor L. leaves (Clusiaceae) in mice. Methods: Phytochemical characterization was performed by Gas Chromatography/Mass Spectrometry. Antinociceptive effect was evaluated using acetic acid, formalin, hot plate, and capsaicin models. Mechanical hypernociception was induced by intraplantar carrageenan, tumor necrosis factor α (TNFα) and prostagladin E2 (PGE2) and responses were measured after 3 h of injection. Results: Mass Spectrometry analysis allowed the identification of 16 compounds. Fatty acid derivatives, steroids, triterpenoids, and vitamin E were the main findings. The most abundant sterol was β-sitosterol (14.04%); followed by the triterpenes α-amyrin (11.94%), and β-amyrin (7.82%). Vitamin E represented the 8.44% of the total identified compounds. The evaluation of the acetic acid-induced nociception model showed that the extract was effective in reducing pain in a dose-dependent manner. This resulted in a maximal inhibition of 53 ± 4%. The extract was also effective in other pain models. Additionally, the extract presented a considerable inhibition of paw mechanical hypernociception. Conclusions: The data suggest that the antinociceptive effect of Clusia minor occurs by interaction of various mechanisms; which probably take places via central and peripheral pathway. Therefore, modulating the inflammatory and neurogenic pain.